2002
DOI: 10.1007/s00436-002-0723-3
|View full text |Cite
|
Sign up to set email alerts
|

Fasciola hepatica alters coagulation parameters in sheep plasma in vivo and in vitro

Abstract: The blood-sucking activities of the liver fluke, Fasciola hepatica, are likely to cause alterations in coagulation during the course of infection; and the effect of F. hepatica on various coagulation parameters was studied during the course of acute and chronic fasciolosis of sheep over a period of 17 weeks. Whole blood and plasma samples from infected sheep (with 800 metacercariae each) and uninfected controls were collected weekly until 17 weeks post-infection (w.p.i.) and the activated partial thromboplasti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 19 publications
1
5
0
Order By: Relevance
“…The results obtained in the present study revealed that AsL3C and AsL3ES inhibited the intrinsic, extrinsic and/or common pathways of the coagulation cascade before the transformation of fibrinogen into fibrin, since the APTT and PT assays were significantly altered in the presence of both antigenic extracts, but no significant change was found in the TT assay. These results correlate with those obtained in other studies using similar methodologies for both helminth and arthropod parasites [33][34][35][36][37] as well as reinforce the studies developed with the adult worms of A. suum and its closely related species A. lumbricoides during the 1980s and 1990s [38,39].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The results obtained in the present study revealed that AsL3C and AsL3ES inhibited the intrinsic, extrinsic and/or common pathways of the coagulation cascade before the transformation of fibrinogen into fibrin, since the APTT and PT assays were significantly altered in the presence of both antigenic extracts, but no significant change was found in the TT assay. These results correlate with those obtained in other studies using similar methodologies for both helminth and arthropod parasites [33][34][35][36][37] as well as reinforce the studies developed with the adult worms of A. suum and its closely related species A. lumbricoides during the 1980s and 1990s [38,39].…”
Section: Discussionsupporting
confidence: 90%
“…This mechanism could occur in the AsL3 immediate intravascular habitat or at a systemic level, since similar results were obtained in this study by both their cuticle and excretory/secretory products. Therefore, this strategy could help the parasite to migrate, evade the host immune system and survive, as it has been postulated for other nematode and trematode parasites [31,35,37,60]. In addition, coagulation inhibition by AsL3 could contribute to aggravate the pathological processes produced in the infected pigs.…”
Section: Discussionmentioning
confidence: 95%
“…A cardinal sign of fascioliasis is anaemia, particularly as a consequence of a large fluke burden, which often significantly affects the health and productivity of animals. Several studies have shown evidence supporting the significant negative effect that Fasciola has on metabolic mechanisms associated iron and iron-binding capacity [ 35 ], coagulation [ 37 ] and/or various biochemical parameters in blood [ 71 ], providing insights into the consequences of and responses to major blood loss in infected animals. In the present study, we infected sheep with a relatively small number (n = 180) of metacercariae.…”
Section: Discussionmentioning
confidence: 99%
“…Cellular changes in the infected liver are associated with a disruption of the mitochondrial electron transport chain, and a substantial loss of cytochrome P450 activity and glycogen content in the left lobe [ 3 ]. Physiological changes in infected animals can include glycaemia [ 33 ], lipidaemia [ 34 ], a reduction in plasma ascorbic acid [ 35 ] and testosterone catabolism [ 36 ] as well as an increase in iron and iron-binding capacity [ 35 ], and a variable effect on coagulation [ 37 ]. However, the specific molecular mechanisms underpinning these changes are not well understood.…”
Section: Introductionmentioning
confidence: 99%
“…In sheep, liver fluke infection affects productivity and welfare [3]. It is a predisposing risk factor for mastitis [6] and drop in coagulation parameters [7]. The ingestion of large numbers of infective stages of the parasite can cause a highly pathogenic sub-acute presentation in lambs, characterised by hepatic haemorrhage and lesions, resulting in sudden death [1, 8].…”
Section: Introductionmentioning
confidence: 99%